Bacteriocins from lactic acid bacteria: strategies for the bioprotection of dairy foods - Pujato, Silvina Alicia; Mercanti, Diego Javier; Briggiler Marcó, Mariángeles; Capra, María Luján; Quiberoni, Andrea; Guglielmotti, Daniela Marta (Frontiers in Food Science and Technology, 2024)
Lactic acid bacteria (LAB), essential in fermenting milk, produce an array of antimicrobial compounds, notably bacteriocins, which contribute to the extended shelf life of dairy goods. Bacteriocins, ribosomally synthesized peptides, display broad or narrow-spectrum antimicrobial activity, thus holding promise in food preservation. The classification of LAB bacteriocins is intricate, reflecting evolving genomic insights and biosynthesis mechanisms. Strategies for integrating bacteriocins into dairy products include purified forms, bacteriocin-producing LAB, and bacteriocin-containing fermentates, each with distinct advantages and considerations. Optimization of fermentation conditions, encompassing time, temperature, pH, and culture medium, is essential for maximizing bacteriocin production. This optimization facilitates enhanced quality and safety of fermented dairy items, aligning with the growing consumer preference for natural, minimally processed foods. Furthermore, the incorporation of bacteriocins into a hurdle approach alongside thermal and non-thermal treatments holds promise for augmenting food bioprotection while reducing reliance on chemical preservatives. This comprehensive overview underscores the potential of LAB bacteriocins as a natural, effective alternative to conventional food preservatives, offering insights into their application and optimization in dairy product preservation.